Aflatoxin in chili peppers in Nigeria: extent of contamination and control using atoxigenic aspergillus flavus genotypes as biocontrol agents - Ezekiel, C.N.; Ortega Beltran, A.; Oyedeji, E.O.; Atehnkeng, J.; Kössler, P.; Tairu, F.; Hoeschle-Zeledon, I.; Karlovsky, P.; Cotty, P.J.; Bandyopadhyay, Ranajit (MDPI, 2019)
Across sub-Saharan Africa, chili peppers are fundamental ingredients of many traditional dishes. However, chili peppers may contain unsafe aflatoxin concentrations produced by Aspergillus section Flavi fungi. Aflatoxin levels were determined in chili peppers from three states in Nigeria. A total of 70 samples were collected from farmers’ stores and local markets. Over 25% of the samples contained unsafe aflatoxin concentrations. The chili peppers were associated with both aflatoxin producers and atoxigenic Aspergillus flavus genotypes. E cacy of an atoxigenic biocontrol product, Aflasafe, registered in Nigeria for use on maize and groundnut, was tested for chili peppers grown in three states. Chili peppers treated with Aflasafe accumulated significantly less aflatoxins than nontreated chili peppers. The results suggest that Aflasafe is a valuable tool for the production of safe chili peppers. Use of Aflasafe in chili peppers could reduce human exposure to aflatoxins and increase chances to commercialize chili peppers in premium local and international markets. This is the first report of the e cacy of any atoxigenic biocontrol product for controlling aflatoxin in a spice crop.